diff --git a/src/differential_equations_2.md b/src/differential_equations_2.md index 2c26674823386ed925899c272b2627de2f0e73bb..a2ca1996723a33fbef9803b4eee308faa861989f 100644 --- a/src/differential_equations_2.md +++ b/src/differential_equations_2.md @@ -10,3 +10,142 @@ For this purpose we make the following definitions, $$y' = \frac{dy}{dx}, \ y'' = \frac{d^2 y}{dx^2}, \ \cdots, \ y^{(n)} = \frac{d^n y}{dx^n}.$$ +In the new notation, a linear $n$-th order differential equation with constant +coefficients reads + +$$y^{(n)} + a_{n-1} y^{(n-1)} + \cdots + a_1 y' + a_0 y = 0. $$ + +!!! info "Linear combination of solutions are still solutions" + + Note that as was the case for first order linear DE's, the propery of + linearity once again means that if $y_{1}(x)$ and $y_{2}(x)$ are both + solutions, and $a$ and $b$ are constants, + + $$a y_{1}(x) + b y_{2}(x)$$ + + then linear combination of the solutions is also a solution. + +In order to solve a higher order linear DE we will present a trick that makes it +possible to map the problem of solving a single $n$-th order linear DE into a +related problem of solving a system of $n$ first order linear DE's. + +To begin, define: + +$$y_{1} = y, \ y_{2} = y', \ \cdots, \ y_{n} = y^{(n-1)}.$$ + +Then, the differential equation can be re-written as + +$$y_1 ' = y_2$$ +$$y_2 ' = y_3$$ +$$ \vdots $$ +$$y_{n-1} ' = y_{n}$$ +$$y_{n} ' = - a_{0} y_{1} - a_{1} y_{2} - \cdots - a_{n-1} y_{n}.$$ + +Notice that together these $n$ equations form a linear first order system, the +first $n-1$ equations of which are trivial. Note that this trick can be used to +reduce any system of $n$-th order linear DE's to a larger system of first order +linear DE's. + +Since we have discussed already the method of solution for first order linear +systems, we will outline the general solution to this system. As before, the +general solution will be the linear combination of $n$ linearly independent +solutions $f_{i}(x)$, $i \epsilon \{1, \cdots, n \}$, which make up a basis for +the solution space. That is the general solution has the form + +$$y(x) = c_1 f_1 (x) + c_2 f_2 (x) + \cdots + c_n f_{n}(x). $$ + +To check that the $n$ solutions form a basis, it is sufficient to verify + +$$ det \begin{bmatrix} +f_1(x) & \hdots & f_{n}(x) \\ +f_1 ' (x) & \hdots & f_{n}'(x) \\ +\vdots & \vdots & \vdots \\ +f^{(n-1)}_{1} (x) & \hdots & f^{(n-1)}_{n} (x) \\ +\end{bmatrix} \neq 0.$$ + +The determinant in the preceding line is called the *Wronski determinant*. In +particular, to determine solutions, we need to find the eigenvalues of + +$$**A** = \begin{bmatrix} +0 & 1 & 0 & \hdots & 0 \\ +0 & 0 & 1 & \hdots & 0 \\ +\vdots & \vdots & \vdots & \hdots & \vdots \\ +-a_0 & -a_1 & -a_2 & \hdots & -a_{n-1} \\ +\end{bmatrix}.$$ + +It is possible to show that + +$$det(**A** - \lambda \mathbbm{1}) = -P(\lambda),$$ + +in which $P(\lambda)$ is the characteristic polynomial of the system matrix $**A**$, + +$$P(\lambda) = \lambda^n + a_{n-1} \lambda^{n-1} + \cdots + a_0.$$ + +As we demonstrate below, the proof relies on the co-factor expansion technique +for calculating a determinant. + +$$- det(**A** - \lambda \mathbbm{1}) = \begin{bmatrix} +\lambda & -1 & 0 & \hdots & 0 \\ +0 & \lambda & -1 & \hdots & 0 \\ +\vdots & \vdots & \vdots & \hdots & \vdots \\ +a_0 & a_1 & a_2 & \hdots & a_{n-1} + \lambda \\ +\end{bmatrix} $$ +$$- det(**A** - \lambda \mathbbm{1}) = \lambda det \begin{bmatrix} +\lambda & -1 & 0 & \hdots & 0 \\ +0 & \lambda & -1 & \hdots & 0 \\ +\vdots & \vdots & \vdots & \hdots & \vdots \\ +a_1 & a_2 & a_3 & \hdots & a_{n-1} + \lambda \\ +\end{bmatrix} + (-1)^{n+1}a_0 det \begin{bmatrix} +-1 & 0 & 0 & \hdots & 0 \\ +\lambda & -1 & 0 & hdots & 0 \\ +\vdots & \vdots & \vdots & \hdots & \vdots \\ +0 & 0 & \hdots & \lambda & -1 \\ +\end{bmatrix}$$ +$$- det(**A** - \lambda \mathbbm{1}) = \lambda det \begin{bmatrix} +\lambda & -1 & 0 & \hdots & 0 \\ +0 & \lambda & -1 & \hdots & 0 \\ +\vdots & \vdots & \vdots & \hdots & \vdots \\ +a_1 & a_2 & a_3 & \hdots & a_{n-1} + \lambda \\ +\end{bmatrix} + (-1)^{n+1} a_0 (-1)^{n-1}$$ +$$- det(**A** - \lambda \mathbbm{1}) = \lambda det \begin{bmatrix} +\lambda & -1 & 0 & \hdots & 0 \\ +0 & \lambda & -1 & \hdots & 0 \\ +\vdots & \vdots & \vdots & \hdots & \vdots \\ +a_1 & a_2 & a_3 & \hdots & a_{n-1} + \lambda \\ +\end{bmatrix} + a_0$$ +$$- det(**A** - \lambda \mathbbm{1}) = \lambda (\lambda (\lambda \cdots + a_2) + a_1) + a_0$$ +$$- det(**A** - \lambda \mathbbm{1}) = P(\lambda).$$ + +In the second last line of the proof we indicated that the method of co-factor +expansion demonstrated is repeated an additional $n-2$ times. This completes the +proof. + +With the characteristic polynomial, it is possible to write the differential +equation as + +$$P(\frac{d}{dx})y(x) = 0.$$ + +To determine solutions, we need to find $\lambda_i$ such that $P(\lambda_i) = 0$. +By the fundamental theorem of algebra, we know that $P(\lambda)$ can be written +as + +$$P(\lambda) = \overset{l}{\underset{k=1}{\Sigma}} (\lambda - \lambda_k)^{m_k}.$$ + +In the previous equation $\lambda_k$ are the k roots of the equations, and $m_k$ +is the multiplicity of each root. Note that the multiplicities satisfy +$\overset{l}{\underset{k=1}{\Sigma}} m_k = n$. + +If the multiplicity of each eigenvalue is one, then solutions which form the +basis are then given as: + +$$f(x) = e^{\lambda_1 x}, \ e^{\lambda_2 x}, \ \cdots, \ e^{\lambda_n x}.$$ + +If there are eigenvalues with multiplicity greater than one, the the solutions +which form the basis are given as + +$$f(x) = e^{\lambda_1 x}, \ x e^{\lambda_1 x} , \ \cdots, \ x^{m_{1}-1} e^{\lambda_1 x}, \ etc.$$ + + + + + \ No newline at end of file